Aluminum nitride-aluminum oxide heat-conducting filler powder and preparation method thereof
Through a new preparation method, high-temperature nitriding operation is avoided, and the thermal conductivity and stability of aluminum nitride-alumina thermal filler is successfully improved, and the problem of insufficient thermal conductivity of existing thermal composite materials is solved, thereby achieving low-cost and efficient thermal filler preparation.
Patent Information
- Application Number
- CN202411998525.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The thermal conductivity of existing thermal composite materials is limited by the low thermal conductivity of oxide fillers, which is difficult to meet the needs of the future heat dissipation material market. At the same time, aluminum nitride has high cost and complex process as a high thermal conductivity material.
Through a new preparation method, Al2O3 slurry and AlN slurry are prepared respectively. The Al2O3 slurry is sprayed and granulated, and then mixed with the AlN slurry for spray granulation again, avoiding high-temperature nitriding operation, and the process is simple and cost is low.
The high thermal conductivity, sphericality and stability of aluminum nitride-alumina thermal filler are achieved, and the thermal conductivity can reach 70W/m·K and above, and the process is simple and the cost is low.
Smart Images

Figure CN119799286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive materials, and in particular to an aluminum nitride-aluminum oxide thermal conductive filler powder and a preparation method thereof. Background Art
[0002] With the development of modernization, the miniaturization and integration of electronic products are becoming increasingly higher. Heat dissipation has become an important issue in the development of the industry, and thermal conductive composite materials such as thermal interfaces that determine the heat dissipation effect have received more and more attention. Currently, commercial thermal conductive composite materials are generally composed of plastic organic matter and thermal conductive fillers. Since the thermal conductivity of organic matter is very low, generally less than 0.5 W / m·K, the thermal conductivity of thermal conductive composite materials is mainly determined by the thermal conductive filler.
[0003] The most widely used fillers in the market are oxide fillers represented by A12O3, etc. However, the thermal conductivity of oxide fillers is relatively low. Due to this limitation, it is difficult to prepare thermally conductive composite materials that meet the market demand for future heat dissipation materials. As a new generation of electronic ceramic materials, aluminum nitride has a theoretical thermal conductivity of 320 W / m·K. The thermal conductivity of aluminum nitride prepared in the laboratory can currently reach 260 W / m·K, and the room temperature resistivity is greater than 10 14 Ω·m, with good insulation properties, secondly, it also has the advantages of high strength, thermal expansion coefficient similar to silicon, resistance to plasma erosion, good insulation performance and low dielectric constant. Studies have shown that when AlN is used instead of commonly used A12O3 as a thermal conductive filler and compounded with epoxy resin, its thermal conductivity is nearly 2.7 times that of A12O3 when the solid content reaches 68.5 vol%. However, although the thermal conductivity of pure aluminum nitride is much higher than that of aluminum oxide, the cost of using aluminum nitride to prepare thermal conductive fillers is much higher than that of aluminum oxide, and the process is complex and difficult, requiring reaction at high temperature, and difficult to promote commercially. The use of aluminum nitride coating to prepare thermal conductive fillers has become a new research direction.
[0004] At present, there have been many reports on aluminum nitride coating other powders (such as A12O3). For example, the invention patents with publication numbers CN104710792A and CN109868118A both disclose a core-shell structure of aluminum nitride-alumina thermal conductive filler, but they all need to be nitrided at a high temperature above 1300°C, the process conditions are difficult, the cost is high, and it is easy to have insufficient reaction, produce by-products, and thus affect the thermal conductivity. The invention patent with publication number CN 109369158 A discloses "an insulating thermal conductive composite ceramic powder, its preparation method and application, and insulating thermal conductive coating", and its preparation method includes the following steps: first mix the aluminum oxide with a solvent, and then mix it with the aluminum nitride, the adhesive, and the dispersant in turn to form a slurry, and then spray granulate. This preparation method is simple, efficient, and pollution-free, and can improve the probability of stable compounding of powders and the yield of powders. However, this patent adopts a method of mixing AlN and Al2O3 slurry and then ball milling. The mass ratio of AlN to Al2O3 used is close to 1:1, and the cost is relatively high.
[0005] Based on this, it is of great significance to provide a new low-cost method for preparing aluminum nitride-aluminum oxide thermal conductive filler and ensure the excellent performance of the finally prepared filler. Summary of the invention
[0006] The invention provides a novel preparation method of aluminum nitride-aluminum oxide thermal conductive filler powder, which does not require nitriding operation and has simple process and low cost.
[0007] The invention also provides a heat-conducting filler powder of aluminum nitride-aluminum oxide, which has better thermal conductivity, sphericity and stability.
[0008] The present invention provides a method for preparing aluminum nitride-aluminum oxide thermal conductive filler powder, comprising the following steps:
[0009] Al2O3 slurry and AlN slurry are prepared respectively, wherein both Al2O3 slurry and AlN slurry contain solvent, surface modifier, dispersant and binder; wherein in the Al2O3 slurry, the mass ratio of Al2O3 to dispersant and binder is (75-200):1:(10-12); in the AlN slurry, the mass ratio of AlN to dispersant and binder is (75-200):1:(10-12), the mass ratio of raw material Al2O3 to AlN is (5-7):(3-4), the particle size of raw material Al2O3 in the Al2O3 slurry is 20-25 μm, and the particle size of AlN in the AlN slurry is 1-2 μm;
[0010] First, the Al2O3 slurry is subjected to the first spray granulation, and the granulated material is debonded, and large particles are removed through a 325-mesh screen, and fine particles are removed through a 625-mesh screen to obtain Al2O3 powder; then the Al2O3 powder is mixed into the AlN slurry for the second spray granulation, the granulated material is debonded, and large particles are removed through a 270-mesh screen, and fine particles are removed through a 500-mesh screen to obtain AlN-Al2O3 thermal conductive filler; wherein, during the spray granulation, the speed of the centrifugal atomizer is 8000-14000 r / min, the inlet temperature is 180-240°C, the outlet temperature is 90-130°C, the cavity pressure is 1.5-3bar, and the atomizer flow rate is 3-6m 3 / h.
[0011] The method for preparing the aluminum nitride-aluminum oxide thermal conductive filler described above further includes the step of ball milling the Al2O3 slurry and the AlN slurry.
[0012] According to the preparation method of aluminum nitride-alumina thermal conductive filler described above, the ball milling conditions are: ball milling speed of 300~500 r / min, ball milling time of 4~6 h; wherein, the ball milling medium with a diameter of 12-22 mm is used for ball milling of Al2O3 slurry, and the mass ratio of the ball milling medium to Al2O3 in the Al2O3 slurry is 3: (2~9); the ball milling medium with a diameter of 2-8 mm is used for ball milling of AlN slurry, and the mass ratio of the ball milling medium to AlN in the Al2O3 slurry is 3: (2~9).
[0013] According to the above-mentioned preparation method of aluminum nitride-alumina thermal conductive filler, in Al2O3 slurry, the mass ratio of Al2O3 to dispersant and binder is (150~200):1:(10~12); in AlN slurry, the mass ratio of AlN, dispersant and binder is (150~200):1:(10~12); the mass ratio of raw material Al2O3 to AlN is (5~7):(3~4).
[0014] According to the above-mentioned method for preparing the aluminum nitride-aluminum oxide thermal conductive filler, the solvent is water.
[0015] According to the above-mentioned method for preparing the aluminum nitride-aluminum oxide thermal conductive filler, the surface modifier is selected from one or both of phosphoric acid and aluminum dihydrogen phosphate.
[0016] According to the above-mentioned method for preparing the aluminum nitride-aluminum oxide thermal conductive filler, the concentration of the surface modifier in the solvent is 1-5wt%.
[0017] According to the above-mentioned method for preparing aluminum nitride-aluminum oxide thermal conductive filler, the dispersant is selected from one or more of stearic acid, hexenyl bisstearamide, tristearate glyceryl, and polyethylene glycol.
[0018] According to the above-mentioned method for preparing aluminum nitride-aluminum oxide thermal conductive filler, the binder is selected from one or more of ethylene-vinyl acetate, polyvinyl alcohol, rubber gasoline, phenolic resin, and epoxy resin.
[0019] According to the above-mentioned preparation method of aluminum nitride-alumina thermal conductive filler, the conditions for debinding the granulated material are 400-1000°C debinding treatment for 2-6 hours.
[0020] The present invention also provides an aluminum nitride-oxide thermal conductive filler, which is prepared by any of the above methods.
[0021] The preparation method of aluminum nitride-alumina thermal conductive filler provided by the present invention comprises the following steps: firstly preparing Al2O3 slurry and AlN slurry respectively, first granulating the Al2O3 slurry, and then mixing it with AlN slurry for re-granulation; by controlling the particle size and dosage of the raw materials, the aperture of the sieve for screening after granulation, and the granulation conditions, it is ensured that the obtained thermal conductive filler has better thermal conductivity than the existing similar fillers; and the preparation method avoids high-temperature nitriding operation and has a simple process.
[0022] The aluminum nitride-aluminum oxide thermal conductive filler powder of the present invention has better thermal conductivity, sphericity and stability, among which the thermal conductivity can reach 70 W / m·K or above. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention provides a process flow for preparing the aluminum nitride-aluminum oxide thermal conductive filler;
[0024] Figure 2 The SEM images of the aluminum nitride-alumina filler and AlN powder prepared in Example 1 of the present invention are shown in FIG. a, wherein FIG. b is a SEM image of the aluminum nitride-alumina filler finally prepared, and FIG. 4 is a SEM image of the AlN after ball milling;
[0025] Figure 3 This is a SEM image of another cross section of the aluminum nitride-aluminum oxide filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The present invention provides a method for preparing an aluminum nitride-aluminum oxide thermal conductive filler, and the preparation process thereof is as follows: Figure 1As shown, the specific steps include:
[0028] Al2O3 slurry and AlN slurry are prepared respectively, and both Al2O3 slurry and AlN slurry contain solvent, surface modifier, dispersant and binder; wherein, in Al2O3 slurry, the mass ratio of Al2O3 to dispersant and binder is (75-200):1:(10-12); in AlN slurry, the mass ratio of AlN to dispersant and binder is (75-200):1:(10-12), the mass ratio of raw material Al2O3 to AlN is (5-7):(3-4), the particle size of raw material Al2O3 in Al2O3 slurry is 20-25 μm, and the particle size of AlN in AlN slurry is 1-2 μm.
[0029] First, the Al2O3 slurry is subjected to the first spray granulation, and the granulated material is debonded, and large particles are removed through a 325-mesh screen, and fine particles are removed through a 625-mesh screen to obtain Al2O3 powder; then the Al2O3 powder is mixed with the AlN slurry for the second spray granulation, and the granulated material is debonded, and large particles are removed through a 270-mesh screen, and fine particles are removed through a 500-mesh screen to obtain AlN-Al2O3 thermal conductive filler; wherein, during the spray granulation, the speed of the centrifugal atomizer is 8000-14000 r / min, the inlet temperature is 180-240°C, the outlet temperature is 90-130°C, the cavity pressure is 1.5-3bar, and the atomizer flow rate is 3-6m 3 / h.
[0030] Different from the method of preparing aluminum nitride-aluminum oxide filler by high-temperature nitriding treatment or mixing the two in the prior art, the present invention prepares Al2O3 slurry and AlN slurry separately, and then sprays and granulates the Al2O3 slurry, debinds it, and controls the particle size of the primary granulated material through a specific screen to prepare Al2O3 powder (whose particle size is about 20-47μm), and then mixes the Al2O3 powder obtained after spray granulation and debinding with AlN slurry, and sprays it again. Granulation, debinding and screening through a specific sieve to obtain AlN-Al2O3 thermal conductive filler (whose particle size is about in the range of 25-53μm). By controlling the raw material particle size, dosage, sieve aperture of screening after granulation and granulation conditions, it is ensured that the obtained thermal conductive filler has better thermal conductivity than existing similar fillers. The preparation method avoids high-temperature operation and has a simple process. The aluminum nitride-alumina thermal conductive filler prepared by the method has a high thermal conductivity, which can reach 70W / m·K or above.
[0031] It should be noted that in the present invention, the amount of Al2O3 and AlN is determined according to the theoretical amount of AlN coated Al2O3. The amount of AlN is added 10-20wt% more than the theoretical amount. The purpose is to control the final filler and ensure that most of the final filler is coated particles.
[0032] It is understandable that in practical applications, in order to obtain fillers of target size, the slurry is usually subjected to ball milling treatment, which ensures uniform particle size distribution on the one hand and facilitates subsequent high yield of fillers of target particle size on the other hand. During ball milling, the ball milling speed is usually controlled between 300 and 500 r / min, and the ball milling time is 4 to 6 h. For example, in some specific embodiments, the ball milling speed is 300 r / min and the ball milling time is 5 h; in other specific embodiments, the ball milling speed is 400 rpm and the ball milling time is 6 h; in other specific embodiments, the ball milling speed is 500 rpm and the ball milling time is 5 h.
[0033] Furthermore, when ball-milling Al2O3 slurry, a ball-milling medium with a diameter of 12-22 mm is used, and the mass ratio of the ball-milling medium to Al2O3 in the Al2O3 slurry is 3:(2~9); when ball-milling AlN slurry, a ball-milling medium with a diameter of 2-8 mm is used, and the mass ratio of the ball-milling medium to AlN in the Al2O3 slurry is 3:(2~9).
[0034] Further research also found that when the mass ratio of Al2O3 to dispersant and binder in Al2O3 slurry is (150~200):1:(10~12); in AlN slurry, the mass ratio of AlN, dispersant and binder is (150~200):1:(10~12); and the mass ratio of raw materials Al2O3 to AlN is (5~7):(3~4), the thermal conductivity of the obtained filler is better, reaching 110~130 W / m·K, which is nearly 650% higher than that of traditional Al2O3 thermal conductive fillers (17 W / m·K), much higher than the core-shell structured AlN / Al2O3 thermal conductive fillers in the prior art (CN104710792 A, CN109868118 A, CN109369158 A), and similar to the thermal conductivity of commercial AlN thermal conductive filler powder (120~180 W / m·K).
[0035] For example, in some specific embodiments, in the Al2O3 slurry, the mass ratio of Al2O3 to the dispersant and binder is 180:1:11; in the AlN slurry, the mass ratio of AlN, dispersant and binder is 150:1:10; and the mass ratio of raw material Al2O3 to AlN is 5:3. In other specific embodiments, in the Al2O3 slurry, the mass ratio of Al2O3 to the dispersant and binder is 200:1:12; in the AlN slurry, the mass ratio of AlN, dispersant and binder is 180:1:10; and the mass ratio of raw material Al2O3 to AlN is 7:4.
[0036] It is understood that the Al2O3 slurry and AlN slurry in the present invention not only contain Al2O3 or AlN itself, but also must include a solvent, a surface modifier, a dispersant and a binder. In addition, a plasticizer and a defoaming agent may be appropriately added.
[0037] When preparing the slurry, the order of adding the components in the slurry is not restricted. For example, the surface modifier can be added to the solvent first, and then the Al2O3 powder (or AlN powder), dispersant and binder are added in sequence. Alternatively, the components can be added to the solvent at the same time.
[0038] The solvent used in preparing the slurry can be a commonly used solvent for preparing aluminum nitride-alumina thermal conductive fillers, such as water and anhydrous ethanol. Among them, water is preferably used as the solvent. When pure water is used as the solvent, it is environmentally friendly, safe and low in cost. Compared with alcohol-based spray granulation, there is no safety hazard at all.
[0039] The purpose of the surface modifier is to prevent the AlN powder from hydrolyzing. The selection of the surface modifier is not limited, and a conventional surface modifier can be selected. For example, in some specific embodiments, the surface modifier is selected from one or both of phosphoric acid and aluminum dihydrogen phosphate, and the concentration of the surface modifier can be a conventional concentration, usually 1-5wt% in the solvent.
[0040] Dispersants are a component that can reduce the aggregation of solid or liquid particles in a dispersion system and keep the dispersion system relatively stable. The selection of dispersants is not limited, and conventional dispersants can be selected. For example, in some specific embodiments, the dispersant is selected from one or more of stearic acid, hexenyl bis stearamide, tristearate glyceryl, and polyethylene glycol.
[0041] The binder is used as a bonding component, and its selection is not limited, and conventional binders can be selected. For example, conventional binders such as ethylene vinyl acetate (EVA), polyvinyl alcohol (PVA), PVP, rubber gasoline, phenolic resin and epoxy resin can be selected. In some specific embodiments, the binder is selected from one or more of rubber gasoline, EVA, phenolic resin and epoxy resin.
[0042] The purpose of debinding is to remove organic matter from the granulated material to prevent it from hindering the formation of the AlN-Al2O3 structure. Therefore, the granulated material needs to be debinded after each granulation. The debinding conditions can completely burn off the organic matter in the granulated material. Usually, the debinding treatment is 400~1000℃ for 2~6 hours.
[0043] For example, in some specific embodiments, after the first spray granulation, the conditions for debinding of the granulated material are: debinding at 800°C and curing treatment for 6 hours, and after the second spray granulation, the conditions for debinding of the granulated material are: debinding at 600°C for 6 hours. In other specific embodiments, after the first spray granulation, the conditions for debinding of the granulated material are: debinding at 700°C and curing treatment for 3 hours, and after the second spray granulation, the conditions for debinding of the granulated material are: debinding at 700°C for 3 hours. In other specific embodiments, after the first spray granulation, the conditions for debinding of the granulated material are: debinding at 500°C and curing treatment for 6 hours, and after the second spray granulation, the conditions for debinding of the granulated material are: debinding at 700°C for 6 hours.
[0044] The present invention also provides an aluminum nitride-aluminum oxide thermal conductive filler powder, which is prepared by the above method.
[0045] The thermal conductive filler powder has the advantages of low cost, high thermal conductivity, simple steps, etc. Its density is 3.3-3.5g / cm 3 , the thermal conductivity can reach 70W / m·K and above.
[0046] Hereinafter, the preparation method of the aluminum nitride-aluminum oxide thermal conductive filler powder of the present invention and the prepared filler powder are introduced in detail in conjunction with specific embodiments.
[0047] In the following embodiments, the density is detected by the Archimedes displacement method. The Archimedes displacement method is a density test method based on the Archimedes principle. The basic principle is that when an object is immersed in a liquid, the weight of the liquid displaced is equal to the weight of the object itself. The density of the filler powder is calculated by measuring the weight change of the liquid before and after the filler powder is immersed in the liquid.
[0048] The thermal conductivity test method is: the filler powder is pressed into small discs using a hydraulic device, and then the thermal conductivity is tested using a German NETZSCH LFA-467 thermal conductivity meter.
[0049] The particle size of the raw material Al2O3 used in the following examples and comparative examples is 20-25 μm, and the particle size of the raw material AlN is 1-2 μm.
[0050] Example 1
[0051] This embodiment provides a method for preparing aluminum nitride-aluminum oxide thermal conductive filler powder, comprising the following steps:
[0052] Preparation of Al2O3 slurry: 900 g of alumina powder, 55 g of binder ethylene vinyl acetate (EVA), 5 g of dispersant polyethylene glycol, and 900 g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate are placed in a ball mill to obtain Al2O3 water-based slurry. 900 g of agate balls with a particle size of 20 mm are added to the above Al2O3 water-based slurry, and the ball mill speed is controlled to 300 r / min for ball milling for 5 hours.
[0053] Preparation of AlN slurry: 540 g of aluminum nitride powder, 36 g of binder ethylene-vinyl acetate (EVA), 3.6 g of dispersant polyethylene glycol, and 540 g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain AlN water-based slurry. 540 g of agate balls with a particle size of 5 mm were added to the above AlN water-based slurry, and the ball milling speed was controlled at 300 r / min for 5 h. The SEM image of the AlN after ball milling is shown in FIG. Figure 2 As shown in b.
[0054] The milled alumina slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 12000r / min, the air inlet temperature was 200℃, the air outlet temperature was 100℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, the collected granules were subjected to debinding and curing treatment at 800℃ for 6 h, and then passed through a 325-mesh sieve to remove large particles, a 625-mesh sieve to remove fine particles, and coarse particles to obtain primary granules.
[0055] The collected primary granulation material was mixed with the aluminum nitride slurry after ball milling, and the mixed slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 8000r / min, the air inlet temperature was 225℃, the air outlet temperature was 115℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, and the collected granules were subjected to debinding treatment at 800℃ for 6 h, and then passed through a 270-mesh sieve to remove large particles, and through a 500-mesh sieve to remove fine particles to obtain AlN-Al2O3 granulated powder.
[0056] The SEM photo of the aluminum nitride-alumina thermal conductive filler prepared in this example is as follows Figure 2 a and Figure 3 As shown by Figure 2 It can be seen from a that the filler has good sphericity. Figure 3 It can be seen that most of the aluminum oxide spherical shells are wrapped with a layer of scaly aluminum nitride shell. Further testing shows that its density is 3.31g / cm 3The thermal conductivity reaches 130 W / m·K, which is similar to the thermal conductivity of the currently commercialized AlN thermal conductive filler powder (120~180 W / m·K).
[0057] Example 2
[0058] This embodiment provides a method for preparing aluminum nitride-alumina thermal conductive filler powder, which is different from Embodiment 1 mainly in that the surface modifier is phosphoric acid, the dispersant is stearic acid, and the binder is polyvinyl alcohol (PVA), and specifically comprises the following steps:
[0059] Preparation of Al2O3 slurry: 1260g of alumina powder, 75g of binder ethylene vinyl acetate (EVA), 6.3g of dispersant polyethylene glycol, and 1200g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain Al2O3 water-based slurry. 2500g of agate balls with a particle size of 20mm were added to the above Al2O3 water-based slurry, and the ball mill speed was controlled to 500 r / min for ball milling for 5 hours.
[0060] Preparation of AlN slurry: 720 g of aluminum nitride powder, 44 g of binder ethylene vinyl acetate (EVA), 4 g of dispersant polyethylene glycol, and 720 g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain AlN water-based slurry. 1400 g of agate balls with a particle size of 5 mm were added to the above AlN water-based slurry, and the ball mill speed was controlled to 500 r / min for ball milling for 5 h.
[0061] After the ball milling, the milled alumina slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 12000r / min, the air inlet temperature was 200℃, the air outlet temperature was 100℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, the collected granules were subjected to debinding and curing treatment at 800℃ for 6 h, and then passed through a 325-mesh sieve to remove large particles, and through a 625-mesh sieve to remove fine particles, and then coarse particles were removed to obtain primary granules.
[0062] The collected primary granulation material was mixed with the aluminum nitride slurry after ball milling, and the mixed slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 8000r / min, the air inlet temperature was 225℃, the air outlet temperature was 115℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, and the collected granules were subjected to debinding treatment at 600℃ for 6 h, and then passed through a 270-mesh sieve to remove large particles, and passed through a 500-mesh sieve to remove fine particles, to obtain AlN-Al2O3 granulated powder.
[0063] The density of the aluminum nitride-alumina thermal conductive filler prepared in this embodiment is 3.34 g / cm3 , thermal conductivity is 120W / m·K.
[0064] Example 3
[0065] This embodiment provides a method for preparing aluminum nitride-alumina thermal conductive filler powder, which is different from that of embodiment 1 in that the amounts of dispersant and binder are different. The specific method is as follows:
[0066] Preparation of Al2O3 slurry: 900 g of alumina powder, 120 g of binder ethylene vinyl acetate (EVA), 12 g of dispersant polyethylene glycol, and 900 g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain Al2O3 water-based slurry. 900 g of agate balls with a particle size of 20 mm were added to the above Al2O3 water-based slurry, and the ball mill speed was controlled to 300 r / min for ball milling for 5 hours.
[0067] Preparation of AlN slurry: 540 g of aluminum nitride powder, 72 g of binder ethylene vinyl acetate (EVA), 7.2 g of dispersant polyethylene glycol, and 540 g of an aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain AlN water-based slurry. 540 g of agate balls with a particle size of 5 mm were added to the above AlN water-based slurry, and the ball mill speed was controlled to 300 r / min for ball milling for 5 h.
[0068] After the ball milling, the milled alumina slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 12000r / min, the air inlet temperature was 200℃, the air outlet temperature was 100℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, the collected granules were subjected to debinding and curing treatment at 800℃ for 6 h, and then passed through a 325-mesh sieve to remove large particles, and through a 625-mesh sieve to remove fine particles, and then coarse particles were removed to obtain primary granules.
[0069] The collected primary granulation material was mixed with the aluminum nitride slurry after ball milling, and the mixed slurry was sent to the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer was 8000r / min, the air inlet temperature was 225℃, the air outlet temperature was 115℃, the cavity pressure was 2bar, and the atomizer flow rate was 5m 3 / h, and the collected granules were subjected to debinding treatment at 600℃ for 6 h, and then sieved through a 270-mesh sieve to remove coarse particles, and then sieved through a 500-mesh sieve to remove fine particles to obtain AlN-Al2O3 granulated powder.
[0070] The density of the aluminum nitride-alumina thermal conductive filler prepared in this example is 3.30 g / cm 3 , thermal conductivity is 76W / m·K.
[0071] Comparative Example 1
[0072] The difference between this comparative example and Example 1 is that aluminum nitride and aluminum oxide are mixed and then granulated. The specific method is as follows:
[0073] 900g of alumina powder, 900g of aluminum nitride powder, 100g of binder ethylene vinyl acetate (EVA), 10g of dispersant polyethylene glycol, and 1800g of aqueous solution containing 3 wt% aluminum dihydrogen phosphate were placed in a ball mill to obtain a water-based slurry. 1800g of agate balls with a particle size of 20mm were added to the above water-based slurry, the ball mill speed was controlled to 500r / min, and the ball mill mixing time was 8h.
[0074] The mixed slurry is sent into the centrifugal atomizer of the spray dryer through a peristaltic pump. The speed of the centrifugal atomizer is 10000r / min, the air inlet temperature is 220℃, the air outlet temperature is 110℃, the cavity pressure is 2bar, and the atomizer flow rate is 5m 3 / h, the collected granules were subjected to debinding treatment at 800℃ for 6 h, and then sieved through a 270-mesh sieve to remove coarse particles, and then sieved through a 500-mesh sieve to remove fine particles, to obtain AlN-Al2O3 granulated powder with a particle size of 25-50μm.
[0075] The density of the prepared aluminum nitride-alumina thermal conductive filler is 3.30 g / cm 3 , thermal conductivity is 41 W / m·K.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing aluminum nitride-alumina thermal conductive filler powder, characterized in that: The following steps are involved: Prepare Al2O3 slurry and AlN slurry respectively, wherein the Al2O3 slurry and the AlN slurry both contain a solvent, a surface modifier, a dispersant and a binder; Among them, in the Al2O3 slurry, the mass ratio of Al2O3 to the dispersant and the binder is (75~200):1:(10~12); in the AlN slurry, the mass ratio of AlN, the dispersant and the binder is (75~200):1:(10~12), the mass ratio of the raw material Al2O3 to AlN is (5~7):(3~4), the particle size of the raw material Al2O3 in the Al2O3 slurry is 20~25μm, and the particle size of AlN in the AlN slurry is 1~2μm; First, the Al2O3 slurry is subjected to the first spray granulation, and the granulated material is debonded, and large particles are removed through a 325-mesh screen, and fine particles are removed through a 625-mesh screen to obtain Al2O3 powder; then the Al2O3 powder is mixed into the AlN slurry for the second spray granulation, the granulated material is debonded, and large particles are removed through a 270-mesh screen, and fine particles are removed through a 500-mesh screen to obtain AlN-Al2O3 thermal conductive filler; wherein, during the spray granulation, the speed of the centrifugal atomizer is 8000-14000 r / min, the inlet temperature is 180-240°C, the outlet temperature is 90-130°C, the cavity pressure is 1.5-3bar, and the atomizer flow rate is 3-6m 3 / h.
2. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1, characterized in that: The method also includes the step of ball milling the Al2O3 slurry and the AlN slurry; The ball milling conditions are as follows: the ball milling speed is 300~500 r / min, and the ball milling time is 4~6 h; among them, the ball milling medium with a diameter of 12-22 mm is used for ball milling of Al2O3 slurry, and the mass ratio of the ball milling medium to Al2O3 in the Al2O3 slurry is 3:(2~9); the ball milling medium with a diameter of 2-8 mm is used for ball milling of AlN slurry, and the mass ratio of the ball milling medium to AlN in the Al2O3 slurry is 3:(2~9).
3. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1 or 2, characterized in that: In Al2O3 slurry, the mass ratio of Al2O3 to dispersant and binder is (150~200):1:(10~12); in AlN slurry, the mass ratio of AlN, dispersant and binder is (150~200):1:(10~12); the mass ratio of raw material Al2O3 to AlN is (5~7):(3~4).
4. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1 or 2, characterized in that: The solvent is water.
5. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1 or 2, characterized in that: The surface modifier is selected from one or both of phosphoric acid and aluminum dihydrogen phosphate; and / or The concentration of the surface modifier in the solvent is 1-5 wt %.
6. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1 or 2, characterized in that: The dispersant is selected from one or more of stearic acid, hexenyl bisstearamide, tristearate glyceryl, and polyethylene glycol; and / or The binder is selected from one or more of ethylene vinyl acetate, polyvinyl alcohol, rubber gasoline, phenolic resin and epoxy resin.
7. The method for preparing the aluminum nitride-alumina thermal conductive filler powder according to claim 1 or 2, characterized in that: The conditions for debinding the granulated material are 400~1000℃ for 2~6 hours.
8. Aluminum nitride-aluminum oxide thermal conductive filler powder prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Spherical core-shell structured Al2O3 / AlN thermal-conducting powder and high-thermal-conductivity insulating silicone grease and preparation methods thereof
CN104710792A
Insulating thermal conductive composite ceramic powder, preparation method and application thereof and insulating thermal conductive coating
CN109369158A
Preparation method of aluminum nitride-aluminum oxide core-shell structure with high thermal conductivity
CN109868118A